Body Cliff Safety Study Of Double Track Railway With Geostudio Slope/W Analysis - Warikar, Yance Y D; Arifaini, Nur; Siregar, Amril Ma'ruf (Universitas Lampung, 2020)
Double track railway construction area railroad crossing many hills and rivers makes the railroad body located between the slopes of the hill. Around the area, disasters that often occur are landslides caused by increased pore water pressure on the slope resulting a decrease in the shear strength of the soil (c) and the deep shear angle (φ). Therefore in planning the handling of cliffs of railroad tracks it is necessary to analyze the stability of slopes or cliffs so as not to endanger the surrounding environment, especially in railroad transportation. The purpose of the research are: (1) To know the cross section of the safest slope by considering the slope angle, (2) To Find the value of the safe factor for shear and rolling on the slope by using software analysis, (3) To know type of slope safety in accordance with slope conditions. The location of this research was conducted in the Martapura-Giham area which is the location of the construction of double track railroad, Waykanan Regency, Lampung. The method used in the analysis of slope stability is Geostudio Slope/W Analysis by making 3 cross-section slope designs which are then analyzed further. The results of the analysis found that the slope conditions before handling obtained the number of safe factors with ordinary, bishop, and morgenstern methods, respectively 0.730; 0.911; and 0.950. While after handling with sheetpile construction, it was obtained the number of safe factors with ordinary, bishop, and morgenstern methods in a row that is 2,945; 3,633; and No Solution. It can be concluded that the slope condition after handling shows increase in the value of the safe factor by 500%. Keywords: Geostudio Slope/W Analysis, Double track railroad, Cliffs and slope stability.